Cost - Effectiveness Analysis of Chloramphenicol, Ceftriaxone and Cefixime Use in Pediatric Thypoid Fever Patient (Research Conducted at Karsa Husada Batu Hospital) - Ni Made Diah Pramesti Dewi; Ratna Kurnia Illahi; Diana Lyrawati (Brawijaya University, 2019)
Typhoid fever in Indonesia is still high at 1.6% from 0.3% -3%. Typhoid fever can be treated with several alternative of antibiotic therapy that is chloramphenicol, ceftriaxone and cefixime. This research aimed to analyze the cost-effectiveness the usage of chloramphenicol, ceftriaxone and cefixime antibiotic from health care providers perspective. Medical records and direct medical cost for typhoid fever patients aged 6–12 years were analyzed retrospectively from January 2016–December 2018. Samples were 48 patients and used total sampling method. The usage of chloramphenicol, ceftriaxone and cefixime antibiotics are based on length of stay, ie 3–4; 3,125–5; 3,667–6 days. The use of chloramphenicol, ceftriaxone and cefixime antibiotics are based on the duration of fever, ie 1–2; 1,625–3,667; 1-2,667 days. ICER value in Seruni Utama showed that the usage of chloramphenicol required an additional cost of Rp. 91.382,72 to reduce one day of hospitalization compared to cefixime. ICER value in Seruni 1 showed that the usage of chloramphenicol required an additional cost of Rp. 51.018,575 to reduce one day of hospitalization compared to cefixime and Rp. 587.358,81 to reduce one day of fever compared to ceftriaxone. ICER value in Seruni 2 showed that the usage of ceftriaxone required an additional cost of Rp. 118.760,74 to reduce one day of hospitalization and Rp. 374.498,22 to reduce one day of fever compared to cefixime. ICER value in Seruni 3 showed that the usage of chloramphenicol required an additional cost of Rp. 664.304,50 to reduce one day of hospitalization and Rp. 1.650.777,72 to reduce one day of fever compared to cefixime. The usage of chloramphenicol is more cost-effective in Seruni Utama, 1 and 3 and ceftriaxone is more cost-effective in the Seruni 2.